Cultural Challenges in Translating Literary Texts from Uzbek into English - Jovliyeva Nafosat Bahodir qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Annotation: This article explores the cultural difficulties and complexities involved in translating literary works from Uzbek into English. Since literary translation goes beyond linguistic equivalence, translators must convey not only words but also cultural meanings, emotions, and national identity embedded in the source text. The study discusses specific cultural elements such as idioms, proverbs, historical references, and realia that often pose problems in cross-cultural translation. It also analyzes strategies translators use to maintain the authenticity of Uzbek literature while ensuring comprehensibility for English readers. The findings highlight that successful literary translation requires both linguistic mastery and deep intercultural understanding to bridge cultural gaps between Uzbek and English audiences.